Modeling Volatility and Valuing Derivatives Under Anchoring. Issue 73 (September 2014) - Wilmott, Paul; Lewis, Alan L.; Duffy, Daniel J.
<x xml:space="preserve">Abstract</x> We develop a complete‐markets model with volatility smiles, tractability, and intuitive appeal as an anchoring or habit‐formation model. Like traditional stochastic volatility models, it is invariant to a multiplicative scaling of the stock price levels. The anchoring e?ect is that the volatility depends on the relative value of the current stock price compared to its past history, with an exponential weighting.